Improving rock mass quality using bio-grouting - Chua, Lionel Wei Huang (Nanyang Technological University, 2022)
The aim of this project is to investigate the physical characteristics of bio-grouting that are being used to grout rock fractures. Tri-axial Compression tests are carried out on the host rock samples, which are made of Bukit Timah Granite, that are grouted with 2 different bio-grouting materials, normal bio-grout and bio-grout with sand. The test with sand is to see if there is a further decrease the permeability, thus, improving the performance of the grout.